Comparison of Two Types of Combined Measures, STI and U50, for Predicting Speech Intelligibility in Classrooms - Young-Ji CHOI (Archives of Acoustics)
The present study reports on the speech intelligibility as measured by speech transmission index (STI) and useful-to-detrimental sound ratios ($U_{50}$) in university classrooms. Acoustic measurements were made in 12 quietly occupied university classrooms. The measured impulse responses of the classrooms were used to determine the modulation transfer function, $m(F)$, for the STI calculation according to IEC 60268-16. $U_{50}$ values were determined from both signal-to-noise ratios (SNR) and $C_{50}$ values. The mean STI and frequency-weighted $U_{50}$ values for the 12 occupied classrooms were strongly linearly related. The results showed that classrooms with $U_{50}$ values of about +0.5 dB correspond to STI values of 0.60, indicating ‘good’ acoustical conditions for speech intelligibility. The results illustrate that the $U_{50}$ measure can be a more practically useful means of assessing and understanding room acoustics conditions for real speech communication in active classrooms.